2009
DOI: 10.1158/0008-5472.sabcs-09-4094
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole in Combination with Trastuzumab Is Superior to Letrozole Monotherapy as First Line Treatment in Patients with Hormone-Receptor-Positive, HER2- Positive Metastatic Breast Cancer (MBC) – Results of the eLEcTRA Trial.

Abstract: Background: Letrozole (LET) and trastuzumab (TRA) are established agents for the treatment of hormone-receptor (HR) positive metastatic breast cancer (MBC) patients and HER2 positive disease, respectively. The “eLEcTRA” trial was designed to compare the efficacy and safety of LET combined with TRA to LET alone in patients that are both HER2 and HR positive. Furthermore, LET alone was compared in patients with HER2 and HR positive disease vs. those with HER2 negative, HR positive tumors.Methods: In this multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…However, the goal of the trial -proof-of-concept for clinical relevant activity of combination AI plus trastuzumab in patients with resistant disease to single-agent exposure -was achieved with less patients accrued than initially planned due to the surprisingly high CBR in the first 11 patients included. This observation is in concordance with the CBR of 65%, observed in 26 patients with ERC/HERC breast cancers receiving first-line treatment with letrozole and trastuzumab within a randomized trial (Huober et al 2009). Furthermore, this finding is in line with results of the anastrozole plus trastuzumab arm (CBR 43%) of the randomized TAnDEM trial (Kaufman et al 2009) and of another phase II trial using letrozole and trastuzumab (CBR 52%) as first-or second-line therapy (Marcom et al 2007).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the goal of the trial -proof-of-concept for clinical relevant activity of combination AI plus trastuzumab in patients with resistant disease to single-agent exposure -was achieved with less patients accrued than initially planned due to the surprisingly high CBR in the first 11 patients included. This observation is in concordance with the CBR of 65%, observed in 26 patients with ERC/HERC breast cancers receiving first-line treatment with letrozole and trastuzumab within a randomized trial (Huober et al 2009). Furthermore, this finding is in line with results of the anastrozole plus trastuzumab arm (CBR 43%) of the randomized TAnDEM trial (Kaufman et al 2009) and of another phase II trial using letrozole and trastuzumab (CBR 52%) as first-or second-line therapy (Marcom et al 2007).…”
Section: Discussionsupporting
confidence: 88%
“…These trials when interpreted together suggest that single-agent endocrine therapy in HER-2C disease has low efficacy and is clearly inferior to combination therapy (Huober et al 2009, Johnston et al 2009, Kaufman et al 2009). Upfront combination on targeted therapy, especially in elderly patients, patients declining chemotherapy, or without extensive, life-threatening visceral involvement, might become a reasonable treatment option in the near future in light of these trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44][45][46][47][48][49][50][51] Four of these citations 48-51 reporting on two trials [the efficacy and safety of lapatinib combined with letrozole (EGF30008) 49 trial and the efficacy and safety of trastuzumab combined with anastrozole (TAnDEM) 50 trial] met the inclusion criteria and a further trial [efficacy and safety of letrozole combined with trastuzumab (eLEcTRA) 52 trial], reported only as a conference abstract, was also suitable for inclusion following information passed on to the AG by Roche at the NICE consultation meeting in February 2010. Thus, three trials were included in the systematic review.…”
Section: Quantity and Quality Of Research Availablementioning
confidence: 99%
“…All three trials (the EGF30008, 49 the TAnDEM 50 and the eLEcTRA 52 ) were multicentre and multinational trials (between 7 and 29 countries) enrolling post-menopausal patients receiving first-line treatment for mBC; all three trials included patients who had HR+/HER2+ mBC, although the EGF30008 49 and the eLEcTRA 52 also included patients who were HR+/ human epidermal growth factor receptor 2 negative (HER2-). The trials were designed to evaluate the efficacy and safety of the addition of LAP + LET to LET (EGF30008 49 ), TRA + ANA to ANA (TAnDEM 50 ) and TRA + LET to LET (eLeCTRA 52 ).…”
Section: Included Trialsmentioning
confidence: 99%